Immune Activation, Proinflammatory Cytokines, and Conventional Risks for Cardiovascular Disease in HIV Patients: A Case-Control Study in Bahia, Brazil - Brites-Alves, Clara; Luz, Estela; Netto, Eduardo M.; Ferreira, Thalis; Diaz, Ricardo Sohbie; Pedroso, Celia; Page, Kimberly; Brites, Carlos (Frontiers in Immunology, 2018)
Background Cardiovascular events (CVE) are an increasing cause of morbi-mortality for HIV patients. The antiretroviral therapy (ART), persistent immune activation, and life style are factors that can increase CVE for such patients. We performed a case-control study to evaluate the role of coinfections and immune markers associated with CVE. Methods We included patients under ART, with undetectable plasma viral load ≥12 months. Patients presenting any condition of risk for CVE were considered cases, and those without CVE risk conditions were controls. History of viral infections (Epstein–Barr virus, hepatitis C virus, hepatitis B virus, and cytomegalovirus), exposure to antiretroviral drugs, time since HIV diagnosis/under ART, and life style (demographics, weight, smoking, alcohol, and illicit drug use) were assessed. CD4/CD8 nadir and current counts, nadir and current CD4/CD8 ratio, immune activation markers (CD4CD38HLADR, CD8CD38HLADR), and serum levels of eight cytokines [IL-2, IL-4, IL-6, IL-10, tumoral necrosis factor-alpha (TNF-α), interferon gamma, macrophage inflammatory proteins 1 alpha, and interferon-inducing protein (IP-10)] were measured. Results Two-thirds of patients were males. Cases (N = 106) were older (52.8 vs 49.5 years, p = 0.002), had higher levels of creatinine (0.97 vs 0.87 mg/dL, p = 0.002) and IL-6 (0.67 vs 0.52 pg/mL, p = 0.04) than controls (N = 114). There was no difference between groups regarding frequency of CD4CD39HLADR+ or CD8CD38HLADR+ cells. We found a significant correlation (all patients) between increased frequency of CD4CD38HLADR+ cells and levels of IP-10 (r = 0.171, p = 0.02) and TNF-α (r = 0.187, p = 0.01). Levels of IL-6 (r = 0.235, p = 0.02), TNF-α (r = 0.267, p = 0.01), and IP-10 (r = 0.205, p = 0.04) were correlated with CD4CD38HLADR+ cells, in controls. Higher frequency of CD4CD38HLADR+ cells was also correlated with levels of IP-10 (r = 0.271, p = 0.04) in patients presenting with arterial hypertension. Frequency of CD4CD38HLADR+ cells was negatively correlated with levels of IL-2 (r = −0.639, p = 0.01) and IL-6 (r = −0.0561, p = 0.03) in patients with hypercholesterolemia. No association was detected between viral infections or smoking/alcohol use and immune activation markers. Conclusion Our results indicate IL-6 levels are associated with increased CV risk. Activated CD4+ T cells were associated with increased levels of proinflammatory cytokines.